1984
DOI: 10.1252/jcej.17.237
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and correlation of the thermal conductivities for several dense fluids and mixtures.

Abstract: A coaxial cylindrical cell was constructed for measuring thermal conductivities of nine pure fluids (argon, nitrogen, oxygen, helium, carbon dioxide, methane, ethane, ethylene and propane) at temperatures ranging from 25 to 76°C under pressures up to 17.5MPa. Thermal conductivities of two binary mixtures (argon-nitrogen and methane-ethylene) were also measured at 30.6, 50.6 and 76.6°C under pressures up to 9.8 MPa. The apparatus was calibrated with eight kinds of gases. The Stiel-Thodos and Crooks-Daubert corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…6, the thermal conductivity values obtained using the adjusted potential function, λ adj , are compared with those obtained using the unadjusted one, λ unadj , with a large number of experimental data sets, [63][64][65][66][67][68][69][70][71][72][73][74][75] with the zero-density part of the correlation of Marsh et al, 74 and with the recommended reference values of Younglove and Ely. 76 We extrapolated the data of Zheng et al 72 at 323.75 K and the steady-state hot-wire data of Marsh et al 74 to zero pressure. The transient hot-wire data of Marsh et al from the same paper 74 are not included in the comparison because these authors found them to be affected by large systematic errors in the dilute gas phase.…”
Section: B Resultsmentioning
confidence: 99%
“…6, the thermal conductivity values obtained using the adjusted potential function, λ adj , are compared with those obtained using the unadjusted one, λ unadj , with a large number of experimental data sets, [63][64][65][66][67][68][69][70][71][72][73][74][75] with the zero-density part of the correlation of Marsh et al, 74 and with the recommended reference values of Younglove and Ely. 76 We extrapolated the data of Zheng et al 72 at 323.75 K and the steady-state hot-wire data of Marsh et al 74 to zero pressure. The transient hot-wire data of Marsh et al from the same paper 74 are not included in the comparison because these authors found them to be affected by large systematic errors in the dilute gas phase.…”
Section: B Resultsmentioning
confidence: 99%
“…Measurements at higher temperatures were also performed by Senftleben 36, 38 and Senftleben et al 40 in a concentric–cylinder instrument with an uncertainty of 1–2%. Concentric–cylinder instruments were also employed by Zheng et al , 29 Yorizane et al , 30 and Lenoir and Comings 39 with uncertainties of 3, 3, and 1.5% respectively; thus these sets were also included in the primary data sets. The measurements of Lambert et al , 37 performed in a hot–wire apparatus have been successfully employed in previous reference correlations.…”
Section: Thermal-conductivity Correlationsmentioning
confidence: 99%
“…For exactly this reason, all other measurements performed in transient hot–wire or hot–wire instruments in the dilute-gas region were not included in the primary data set. The remaining investigators 29, 30, 36, 38–40 in the primary–data section of Table 1, who performed measurements with different instruments (other than THW) in the low–pressure low–density gas region, were included as primary data in the correlation. These measurements were employed together with Eqs.…”
Section: Thermal-conductivity Correlationsmentioning
confidence: 99%
See 2 more Smart Citations